Roadmap for the scaling up of Agroecology in Colombia - Valdivia Diaz, Merelyn; Le Coq, Jean-François; Daza, Paola Andrea (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
An analysis of existing policies, programs and limiting factors.